Course on tunnel design & construction delegate information, module 1 : 26-30 June, University of Surrey, Guildford, UK. (Thomas Telford, 2006)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a course held at University of Surrey, Guildford on 26-30 June 2006.